Development of tripeptide-cyclotriphosphazene derivatives: In vitro cytotoxicity, genotoxicity studies and molecular docking analysis within ovarian and prostate cancer cell line receptors - Kaplan, Alpaslan; Caliskan, Eray; Capan, Irfan; Tekin, Suat; Hassan, Mohammad N.; Qaoud, Mohammed T.; Gorgulu, Ahmet Orhan (Pergamon-Elsevier Science Ltd, 2024)
Peptide-phosphazene compounds are important compounds of growing interest in biomedical research and have potential therapeutic effects. The tripeptide-cyclotriphosphazenes conjugates were synthesized and analyzed for their molecular docking analysis, visualizing their binding profiles within various cancer cell line receptors and tested in vitro cytotoxic and genotoxic properties. Determining in vitro cytotoxic studies of obtained compounds displayed cytotoxic effect against two selected human cancer cell lines, including ovarian (A2780) and prostate (PC-3), cancer cells. The compound DTAP demonstrated significantly higher efficacy at 100 mu M in the PC-3 cancer cell line compared to the reference drug docetaxel at 50 mu M. Among the tripeptide-phosphazene conjugtates, DTGG demonstrates the most promising anticancer activity with a logIC50 of 1.23 mu M, forming five hydrogen bonds and a favorable salt bridge interaction, along with several hydrophobic interactions, thereby stabilizing its binding within the human ovarian tumor domain based on molecular docking analysis. The derivative DTGP emerges as the most potent among the DTG derivatives, achieving a Delta G model value of -108 kcal/ mol, primarily due to a lc-cationic interaction with the LYS204 amino acid in chain C, which significantly enhances its binding affinity. Additionally, DNA damage studies on human ovarian and prostate cancer cell lines determined that cell death due to DNA damage was the basis of the decrease in cell viability. These results support the evaluation of the compounds as potential drug candidates.
Keywords: Cytotoxicity; Cyclotriphosphazenes; Genotoxicity; Peptides; Synthesis